Acute and long-term outcomes of ST-elevation myocardial infarction in cancer patients. (14th October 2021) - Lange, S A; Feld, J; Kuehnemund, L; Koeppe, J; Makowski, L; Engelbertz, C H; Gerss, J; Droege, P; Ruhnke, T H; Guenster, C H; Freisinger, E; Reinecke, H
Abstract: Background: Myocardial infarctions (MI) and cancer are each very serious morbidities. To evaluate their interaction in the "real world", a retrospective analysis was performed in patients with ST-elevation MI (STEMI) and pre-existing cancer. Methods: Anonymized data from patients admitted to hospital between 2010 and 2017 due to STEMI were analyzed from 24 months before and up to nine years after the index hospitalization by one of Germany's largest statutory Health Insurance Funds (Allgemeine Ortskrankenkasse - AOK). Qualitative data were tested via two-sided Chi-squared test and quantitative data were tested using a two- sided Wilcoxon test. The eight year overall survival (OS) rate was determined with a Kaplan Meier estimator. The endpoint OS was analysed using multivariable Cox-regression model. Results: From 175, 262 STEMI patients, 27, 213 had cancer (15.5%). Most frequent were skin (24.9%), prostate (17.0%), colon (11.0%), breast (10.9%), urinary tract (10.6%), and lung cancer (5.2%). STEMI patients with malignancies were older, presented more often with coronary three-vessel-disease, classical risk factors, atrial arrhythmias, kidney disease, heart failure, cerebrovascular and peripheral artery disease (PAD) (each p<0.001). They showed more often previous MI, percutaneous coronary interventions (PCI), cardiac surgery, and stroke (all p<0.001). Acute PCIs were applied approximately 2–6 percent points less frequently compared to those without (w/o) cancer, with less drug-eluting and more often bare metal stents (all p<0.001). In-hospital adverse events occurred more frequently in cancer. Eight-year survival was 57.3% (95% CI 57.0% – 57.7%) w/o cancer, and ranged between 41.2% and 19.2% in distinct cancer types. Multivariable Cox regression for death during follow-up found e.g. lung cancer (HR 2.04, 95% CI 1.92–2.17), PAD stage 4–6 (HR 1.78, 95% CI 1.72–1.84) and previous stroke (HR 1.44, 95% CI 1.31–1.54) to have the strongest effect, while obesity (HR 0.95, 95% CI 0.93–0.97) was associated with lower mortality (all p<0.001). Conclusion: In this large "real world" health insurance data from Germany, prognosis after STEMI was markedly reduced but differed widely between cancer types. No withholding of revascularization therapies in cancer patients could be observed. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Federal Joint Committee, Innovation Committee (G-BA, Innovationsfonds, number 01VSF18051).